Transparent tissue in solid state for solvent-free and antifade 3D imaging - Hsiao, Fu-Ting; Chien, Hung-Jen; Chou, Ya-Hsien; Peng, Shih-Jung; Chung, Mei-Hsin; Huang, Tzu-Hui; Lo, Li-Wen; Shen, Chia-Ning; Chang, Hsiu-Pi; Lee, Chih-Yuan; Chen, Chien-Chia; Jeng, Yung-Ming; et al. (Nature communications, 2023)
Optical clearing with high-refractive-index (high- n ) reagents is essential for 3D tissue imaging. However, the current liquid-based clearing condition and dye environment suffer from solvent evaporation and photobleaching, causing difficulties in maintaining the tissue optical and fluorescent features. Here, using the Gladstone-Dale equation [( n −1)/density=constant] as a design concept, we develop a solid (solvent-free) high- n acrylamide-based copolymer to embed mouse and human tissues for clearing and imaging. In the solid state, the fluorescent dye-labeled tissue matrices are filled and packed with the high- n copolymer, minimizing scattering in in-depth imaging and dye fading. This transparent, liquid-free condition provides a friendly tissue and cellular environment to facilitate high/super-resolution 3D imaging, preservation, transfer, and sharing among laboratories to investigate the morphologies of interest in experimental and clinical conditions. Current liquid-based optical clearing protocols can suffer from solvent evaporation and photobleaching. Here, the authors develop a solid high-refractive-index polymer to embed mouse and human tissues for clearing and antifade high-resolution 3D imaging.